Impedance-based PZT transducer and fuzzy logic to detect damage in multi-point dressers - Junior, Pedro O. [UNESP]; D’Addona, Doriana M.; Alexandre, Felipe A. [UNESP]; Ruzzi, Rodrigo [UNESP]; Aguiar, Paulo R. [UNESP]; Baptista, Fabricio G. [UNESP]; Bianchi, Eduardo C. [UNESP] (Springer Nature, 2019)
Alternative techniques such as impedance-based lead zirconate titanate (PZT) transducers has emerged as an innovative approach for manufacturing monitoring process, because its flexibility of using low-cost piezoelectric diaphragms and its simple methodology in terms of apparatus by using the electromechanical impedance (EMI). In addition, this technique has been under several improvements due to the advance of artificial intelligent systems. On this point, the use of fuzzy logic systems has been reported in literature as an attractive combination to improve the process performance. Therefore, this study proposes an approach to detect damage in multi-point dresser based on EMI technique incorporating a fuzzy logic system. To this end, a fuzzy model is built considering the information obtained from representative damage indices corresponding to the different damage cases that are generated at the dresser. At the end, authors expected that the dressing operation can be optimized, preventing the operation from being performed with worn or damaged dressers and ensuring quality standards and precision to the grinding process, which have a high benefit to the manufacturing chain.
Keywords: Electromechanical impedance; Fuzzy logic; Grinding process; PZT transducers; Tool condition